Analysis of the Qur’anic Concepts of Mashriq (East), Maghreb (West), Mashriqain (Two Easts), Maghribain (Two Wests), Mashariq (Several Easts) and Maghreb (Several Wests): Observations in Quetta, Pakistan - Muhammad Kassi, Akhtar; Khan Kasi, Aimal (Journal of Quranic Sciences and Research, 2023)
In the current era various scientific facts revealed by the Holy Qur’an have been scientifically tested and acknowledged by the modern scientists. Also scientific knowledge of Earth and related sciences confirms and support the concepts given in the relevant verses of the Holy Qur’an. For example the Holy Qur’an contains verses that reveal the concepts of Mashriq (East), Maghrib (West), Mashriqain (two easts), Maghribain (two wests), Mashariq (several easts) and Magharib (several wests). This paper pinpoints and put forward scientific analysis of these concepts of the Holy Qur’an, compares and summarizes the pre-existing conventional tafaseer (explanations) with the modern scientific judgments and deliberates on their undisputable integrity. we analyzed these concepts, using scientific methodology, on a fixed location (x,y,z = 67.002, 30.1853, 1684 m) in Quetta, Pakistan. It was observed that the timings and positions (azimuths) of sunrise range from its northeastern extreme on 22nd June at 5:45 am, as 63o (NE), to its southeastern extreme on 22nd December at 8:04 am, as 122o (SE), respectively. The timings and positions (azimuths) of sunset range from its northwestern extreme on 22nd June at 7:21 am, as 300o (NW) to its southwestern extreme on 22nd December at 5:15 am, as 242o (SW), respectively. It was observed that the positions and timing of the sunrise and sunset change daily by shifting gradually from their winter to summer extremes and vice versa in a systematic and predictable manner. I conclude that the Qura’nic words Mashriq (east) and Maghrib (west) refers to the spans of horizons between the eastern and western extremes of the sun rises and sets. The words Mashriqain (two easts) and Maghribain (two wests) refer to the two extremes, i.e. northern and southern positions of sunrise and sunset on the eastern and western horizons, on 22nd June (in summer) and 22nd December (in winter), respectively. The words Mashariq (many easts) and Magharib (many wests) simply refer to the numerous positions of the daily sunrise and sunset on the eastern and western horizons. My results are in conformity with the relevant verses and notions of the Holy Qur’an that have been further explained in various tafaseer, with reference to the explanations of Ib-e-Abbas (RAA) and Akrama (RAA).